2021
DOI: 10.1002/htj.22347
|View full text |Cite
|
Sign up to set email alerts
|

Thermally dissipative micropolar hybrid nanofluid flow over a spinning needle influenced by Hall current and gyrotactic microorganisms

Abstract: At industrial level, the study of nanofluid has a significant role in improving various electrical structures and engineering devices because nanofluid has incredible proficiencies and applications, such as cooling of microelectronic and biomedical devices, vehicles, power generation centers, and so forth. By taking into account such remarkable characteristics of nanofluids, the main focus of this study is to investigate and improve mass and thermal flow for micropolar hybrid nanofluid flow upon a spinning nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This process signals an expansion in the thermal conductivity for base fluids, making it more reliable and ongoing. These significant fluids define nanofluids (NFs) with an extensive series of suggestions in several areas of science, as well as technology, with nuclear devices, heat exchangers, solar plates, vehicle heaters, and biotic and organic devices (Usman et al, 2018;Khan et al, 2022a;Khan et al, 2022b;Ahmed et al, 2022;Hassan et al, 2022;Khan et al, 2022c). First, Lee and Eastman presented the idea of NFs in 1995 (Lee et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This process signals an expansion in the thermal conductivity for base fluids, making it more reliable and ongoing. These significant fluids define nanofluids (NFs) with an extensive series of suggestions in several areas of science, as well as technology, with nuclear devices, heat exchangers, solar plates, vehicle heaters, and biotic and organic devices (Usman et al, 2018;Khan et al, 2022a;Khan et al, 2022b;Ahmed et al, 2022;Hassan et al, 2022;Khan et al, 2022c). First, Lee and Eastman presented the idea of NFs in 1995 (Lee et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has observed by the authors that the upper branch of solution has highlighted to be more applicable due to its stable nature. Khan et al [14][15][16] have deliberated an incredible work to discuss the thermal flow improvement for hybrid nanofluid flow by means of different flow geometries and flow conditions. Recently, it has been noticed by the researchers that the suspension of three different types of nanoparticles in a pure fluid can enhance the thermal conductivity of such fluid to the best possible limit.…”
Section: Introductionmentioning
confidence: 99%
“…With the passage of time it has been revealed that the mixing of two distinct nano particulates can further augment the thermal conductivities of different pure fluids. Such fluids are named as hybrid nanofluids as used by various researchers [15][16][17] to augment thermal flow properties of pure fluid. Chu et al [18] reported the MHD time-dependent hybrid nanoparticles flow amid two plates of infinite dimensions subject to effects of variations in shape of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…With the passage of time it has been revealed that the mixing of two distinct nano particulates can further augment the thermal conductivities of different pure fluids. Such fluids are named as hybrid nanofluids as used by various researchers [15–17] to augment thermal flow properties of pure fluid. Chu et al.…”
Section: Introductionmentioning
confidence: 99%